BAGAIMANA REWARD DAN PUNISHMENT MEMBERIKAN PENGARUH TERHADAP KINERJA KARYAWAN? - Hakim, Adi Lukman; Faizah, Erna Nur; Rosiawan, Rizky Wahyudha; Basyah, Muhammad Ali (STIE Mahardhika, 2024)
The development of the business world in the era of advanced globalization has led to higher business competition. The company conducts human resource empowerment to improve the performance of each employee and the company as a whole. PT Mycotech Agro Asia Ponorogo realizes that to improve the performance of its employees, the company must implement applicable rewards and punishments. The purpose of this study is to explain reward, punishment, and performance at PT Mycotech Agro Asia, analyze the effect of reward and punishment on PT Mycotech Agro Asia, and find the most important variables. This study involved 50 production employees, so all samples were taken from the overall population through the total sampling method. Multiple regression analysis was used to analyze the data. The results showed that reward and punishmet had a positive effect on performance at PT Mycotech Agro Asia Ponorogo partially and simultaneously. The coefficient of determination shows that PT Mycotech Agro Asia company benefits from the compensation and punishment variables with 88.8% of the acquisition value. Other variables that affect employee performance other than the variables in the study obtained 22.2% of the remaining value.